Climate warming impact on the deep demersal fish community East of Greenland - Emblemsvåg, Margrete (UiT The Arctic University of Norway, 2022)
This thesis presents a study of the impact of climate warming on deep demersal fish communities East of Greenland, in a transition zone between Atlantic and Arctic waters. Climate change was expected to affect fish community composition and functional characterization via poleward distributional shifts and changes in abundance. To assess the climate driven effects on fish communities, I used long term survey data (1998 – 2016) covering a depth range of nearly 1500m. Data on taxonomic composition and abundance were combined with functional traits information to address temporal changes in diversity, community structure and functional characterization at different depths. The rapid warming registered during the study period was associated with a decline in both taxonomic and functional diversity, with the sharpest negative trends at depths between 300 and 1000m. Overall, the abundance of boreal species with a generalist diet, like greater argentine (Argentina silus) and Tusk (Brosme brosme) increased, whereas the abundance of Arctic fish benthivores like Lycodes spp. and northern wolffish (Anarhichas denticulatus) decreased. Functional reorganization was most pronounced at depths from 300 to 750m. Species living at great depths down to 1000m were affected by climate events detected at the surface, displaying rapid responses that were likely mediated by behaviour. These findings suggest that deep sea demersal species can respond just as fast to environmental change as species living in the shallower waters of shelf seas. The diversity loss was not consistent with the general expectations of a climate driven increase in Arctic marine biodiversity, observed in other high latitude ecosystems. Clearly, regional conditions may decide the climate driven effects on diversity, as the combination of currents and topography East of Greenland seems to inhibit colonization by boreal species. The documented taxonomic and functional reorganization of the fish communities east of Greenland are likely to affect ecosystem ...